Treatment and outcome analysis of patients with ruptured distal anterior cerebral artery aneurysms: a multicenter real-world study - Zhu, Xiaowei; He, Zhen; Wu, Zhuolin; Li, Yang; Zhao, Yan; Wang, Bangyue; Zhang, Nai; Huang, Qiang; Yang, Tao; Yang, Minghao; Li, Jia; Yang, Xinyu; et al. (Frontiers in Neurology, 2024)
Objective To reveal the safety and efficacy of clipping and coiling in patients with ruptured distal anterior cerebral artery aneurysms (DACAA) and to calculate the risk factors affecting the two-year survival rate in follow-up patients. Methods A retrospective study was conducted on the data of 140 patients (21 were lost to follow-up) with DACAA rupture who were treated by neurosurgery at 12 medical centers over a 2-year period, from January 2017 to December 2020. Univariate analysis was used to examine factors contributing to poor patient prognosis and to compare the prognosis of coiling and clipping treatments. Survival analysis was employed to compare survival rates between coiling and clipping, and risk factors affecting patient survival were analyzed using multivariate Cox regression analysis. Results Out of 140 patients with ruptured DACAA, 80 (57.1%) were male, and 60 (42.9%) were female. A total of 111 (79.3%) patients were classified under Hunt-Hess scale grades I-III, while 95 (67.9%) were graded I-III according to the WFNs classification. Among them, 63 (45%) were treated with clipping, and 77 (55%) underwent coiling. Within 2 years of discharge from the hospital, 31 (59.6%) patients who underwent clipping and 54 (80.6%) who underwent coiling had a good prognosis. Multivariate Cox regression analysis revealed that only WFNs classification (I-III) was a protective factor influencing the 2-year survival of patients with ruptured DACAA. Conclusion In the reality of medical practice, neurosurgeons are more likely to choose clipping as the treatment for cases with WFNs classification than or equal to III. There was no difference between clipping and coiling in the two-year prognosis at discharge. High priority should be given to DACAA cases with WFNs grading (I-III), as better outcomes can be achieved. The sample size will continue to be enlarged in the future to obtain more accurate findings. Abstracts for reviews, technical notes, and historical vignettes do not need to be separated into sections. They should begin with a clear statement of the paper’s purpose followed by appropriate details that support the authors’ conclusion(s).